Delineating Genotype × Environment interactions towards durable resistance in mungbean against Cercospora leaf spot (Cercospora canescens) using GGE biplot. (4th December 2019) - Das, Arpita; Gupta, Sanjeev; Parihar, Ashok K.; Singh, Deepak; Chand, Ramesh; Pratap, Aditya; Singha, Kansam Dayamoy; Kushwaha, Kailash Pati Singh
Abstract: Cercospora leaf spot ( Cercospora canescens ) is a major fungal disease which impedes mungbean production worldwide. Presence of wider host range with existence of pathogenic variability creates intricacy towards host‐pathogen dynamics. Moreover, environmental factors having crucial role in augmenting severity of this disease further complicate disease management. An attempt has been made for unfolding genotype x environment interactions towards identifying and validating durable resistant genotypes against cercospora leaf spot in multi‐environment testing. Preliminary screening with 246 genotypes under artificial epiphytotic condition was conducted to extract out a subset of 22 mungbean genotypes for further evaluation in field testing across six environments consecutively for two years. GGE biplot analysis detected significant environmental influence towards genotypic response and confirmed the presence of non‐crossover interaction with incoherent genotypic response, thus advocating the urgency for multi‐location testing. GGE biplot aptly identified "LGG 460" and "COGG 912" as "ideal" and "desirable" genotypes, respectively having durable resistance and genetic homeostasis and thus suggested for their utilization in future resistance breeding programme in mungbean against cercospora leaf spot.